Regional Governance and Lifelong Learning Policies - Federighi, Paolo (Proceedings e report, 2010)
This document constitutes the Comparative Study of the Precoll project - Policies for Regional Cooperation in Lifelong Learning, led by the Università degli Studi di Firenze-Dipartimento di Scienze dell'Educazione e dei Processi Culturali e Formativi / University of Florence-Department of Educational Sciences and Cultural and Training Processes, in partnership with Generalitat de Catalunya (Spain), Junta de Andalucía (Spain), Regione Toscana (Italy), Welsh Assembly Government (United Kingdom), Jämtland County Council (Sweden), NIACE Dysgu Cymru-National Institute of Adult Continuing Education (United Kingdom), Provincia di Livorno Sviluppo Srl (Italy), subcontractor Melius Srl (Italy). EARLALL has been supporting the quality of the work, as well as Cedefop thanks to the regular advice and suggestions provided by Steven Bainbridge.